2014
DOI: 10.1371/journal.ppat.1004124
|View full text |Cite|
|
Sign up to set email alerts
|

SslE Elicits Functional Antibodies That Impair In Vitro Mucinase Activity and In Vivo Colonization by Both Intestinal and Extraintestinal Escherichia coli Strains

Abstract: SslE, the Secreted and surface-associated lipoprotein from Escherichia coli, has recently been associated to the M60-like extracellular zinc-metalloprotease sub-family which is implicated in glycan recognition and processing. SslE can be divided into two main variants and we recently proposed it as a potential vaccine candidate. By applying a number of in vitro bioassays and comparing wild type, knockout mutant and complemented strains, we have now demonstrated that SslE specifically contributes to degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 54 publications
(56 reference statements)
2
62
0
Order By: Relevance
“…SslE encodes a 1,528-amino-acid protein that was initially identified in a reverse vaccinology screen for E. coli proteins that protect against intraperitoneal or intravenous injection of ExPEC (58). Follow-up studies also demonstrated the efficacy of the vaccine in a murine model of ascending urinary tract infection (57). The gene encoding this protein is found in a majority of ExPEC strains and is localized to both the outer membrane (59) and medium, its secretion being dependent on the type II secretion system (T2SS) (58,72).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SslE encodes a 1,528-amino-acid protein that was initially identified in a reverse vaccinology screen for E. coli proteins that protect against intraperitoneal or intravenous injection of ExPEC (58). Follow-up studies also demonstrated the efficacy of the vaccine in a murine model of ascending urinary tract infection (57). The gene encoding this protein is found in a majority of ExPEC strains and is localized to both the outer membrane (59) and medium, its secretion being dependent on the type II secretion system (T2SS) (58,72).…”
Section: Discussionmentioning
confidence: 99%
“…SslE is annotated as a M60-like metallopeptidase domain located between amino acids 1090 and 1386, the latter being widely distributed in bacteria associated with mucosal surfaces (73). The M60-like domain of SslE cleaves the intestinal mucins Muc 2 and 3, an activity that facilitates the access of heat-labile enterotoxin (LT) from enterotoxigenic E. coli (ETEC) to intestinal enterocytes (56) and is necessary for the passage of ExPEC through a synthesized mucin matrix (57,74). Given this knowledge, it is possible that the lack of translocation observed for ExPEC devoid of sslE is because this strain cannot degrade the thick mucus barrier to gain access to the underlying intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar peptidases in the M60-like family were shown to play roles in bacterium-host interactions (41). For example, SslE from E. coli, an outer-surfaceassociated M60 family peptidase, was reported to be important for the colonization of E. coli cells onto the mucosal surfaces (42). More interestingly, in B. cereus, next to the peptidase gene is a gene (bc5056) that encodes a collagen-like adhesion protein (Fig.…”
Section: Ar156 (mentioning
confidence: 99%
“…This approach allows monitoring the progression of the infection in mice (Gahan 2012;Kuklin et al 2003;Melican and Richter-Dahlfors 2009;Plaut et al 2013) or the spatial and temporal Electronic supplementary material The online version of this article (doi:10.1007/s00253-015-7229-2) contains supplementary material, which is available to authorized users. functionality of specific bacterial promoters (Lane et al 2007; Morin and Kaper 2009;Nesta et al 2014). In both cases, the bioluminescent signals are followed over time in the same live mice, without the need to kill them at fixed time points.…”
Section: Introductionmentioning
confidence: 99%